A novel nanoporous bismuth electrode sensor for in situ heavy metal detection. (1st March 2019) - Hwang, Jae-Hoon; Wang, Xiaochen; Zhao, Daoli; Rex, Matthew M.; Cho, Hyoung J.; Lee, Woo Hyoung
Abstract: A novel modified nanoporous bismuth electrode (modified-NPBiE) sensor was prepared by consecutive procedures which consist of bismuth (Bi) and tin (Sn) electroplating, thermal treatment for alloying Bi-Sn film, and selective chemical dealloying of Sn. The newly prepared modified-NPBiE sensor exhibited improved lifetime (2.7 times longer than a conventional nanoporous Bi-filmed electrode with over 40 repeated measurements) sensor with lower relative standard deviation (RSD), indicating enhanced stability and reproducibility for heavy metal detection. Using square wave anodic stripping voltammetry (SWASV), two noticeable peaks were observed at −0.65 V and −0.45 V associated with stripping currents of Cd 2+ and Pb 2+ in 0.1 M acetate buffer solution at pH 4.6, respectively. The calibration curves showed strong correlations with respect to various concentrations of Cd 2+ and Pb 2+ with the limit of detection (LOD) of 1.3 ppb for Cd 2+ and 1.5 ppb for Pb 2+ . The newly modified-NPBiE sensor was then successfully applied for detecting Cd 2+ and Pb 2+ in a tap water environment and exhibited an acceptable performance for measuring heavy metals with a good reliability. Graphical abstract: Highlights: A modified-NPBiE sensor was developed by a separate Bi-Sn electroplating process. Nanoporous Bi structure after selective Sn etching improved sensor stability. The modified-NPBiE sensor showed good reproducibility over 40 times of measurements. The modified-NPBiE sensor successfully measured Cd 2+ and Pb 2+ in a tap water.